(untitled) (Hoboken, NJ, USA, 2008)
This book presents and explains all the techniques which integrate a certain level of intelligence (through intelligent software agents for example) in order to represent knowledge, take appropriate decisions, communicate with other entities and achieve a self-managing network.
Keywords: Trí tuệ nhân tạo,Mạng lưới máy tính,Viễn thông,Telecommunication,Computer networks,Distributed artificial intelligence; Chương trình máy tính,Computer programs